Cohorts and community: a case study of community engagement in the establishment of a health and demographic surveillance site in Malaysia - Pascale Allotey; Daniel D. Reidpath; Nirmala Devarajan; Kanason Rajagobal; Shajahan Yasin; Dharmalingam Arunachalam; Johanna Debora Imelda; Ireneous Soyiri; Tamzyn Davey; Nowrozy Jahan (Taylor & Francis Group, 2014)
Background: Community engagement is an increasingly important requirement of public health research and plays an important role in the informed consent and recruitment process. However, there is very little guidance about how it should be done, the indicators for assessing effectiveness of the community engagement process and the impact it has on recruitment, retention, and ultimately on the quality of the data collected as part of longitudinal cohort studies. Methods: An instrumental case study approach, with data from field notes, policy documents, unstructured interviews, and focus group discussions with key community stakeholders and informants, was used to explore systematically the implementation and outcomes of the community engagement strategy for recruitment of an entire community into a demographic and health surveillance site in Malaysia. Results: For a dynamic cohort, community engagement needs to be an ongoing process. The community engagement process has likely helped to facilitate the current response rate of 85% in the research communities. The case study highlights the importance of systematic documentation of the community engagement process to ensure an understanding of the effects of the research on recruitment and the community. Conclusions: A critical lesson from the case study data is the importance of relationships in the recruitment process for large population-based studies, and the need for ongoing documentation and analysis of the impact of cumulative interactions between research and community engagement.